Development of Questionnaire to Evaluate Students’ Perception about Real and Virtual Refutational Laboratory: A Rasch Measurement Approach - Amin, Andi Moh; Suhandi, Andi; Efendi, Ridwan (Universitas Muhammadiyah Makassar, 2023)
This study aims to develop the questionnaire of students’ perception about the real and virtual refutational laboratory which is a misconception remediation method adapted from refutation text using a new approach i.e., laboratory. This study was a quantitative description that involved 53 students (12 males and 41 females) chosen using purposive sampling. The students were initially given a trial questionnaire after receiving a misconception remediation treatment using a real and virtual laboratory method in different classes. The validity and reliability of the instrument were analyzed using Rasch Model. The analysis result reveals that the Cronbach's alpha was 0.61 (enough category), the item reliability was 0.82 (good category) and the person reliability was 0.31 (less variance in students' answers). Meanwhile, based on the validity test, the raw variance was obtained from measures of 29.4% reaching the minimum criteria range of 20%. The Differential Item Function (DIF) test based on gender results revealed that an item was biased (p=0.0435), whereas, there is no biased instrument based on the kind of class in the Differential Item Function test study. The analysis demonstrates that after correcting and deleting some items that did not match based on its criteria, this instrument may be used to gather information on students’ perception regarding the implementation of laboratory learning methods or the like in a valid and reliable way by the researchers and teachers.